2020
DOI: 10.1007/s10337-020-03900-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Phenotyping Using UPLC–MS and Rapid Microbore UPLC–IM–MS: Determination of the Effect of Different Dietary Regimes on the Urinary Metabolome of the Rat

Abstract: A rapid reversed-phase gradient method employing a 50 mm × 1 mm i.d., C18 microbore column, combined with ion mobility and high-resolution mass spectrometry, was applied to the metabolic phenotyping of urine samples obtained from rats receiving different diets. This method was directly compared to a "conventional" method employing a 150 × 2.1 mm i.d. column packed with the same C18 bonded phase using the same samples. Multivariate statistical analysis of the resulting data showed similar class discrimination f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Like many others [39][40][41], we have observed that the addition of IM provides many advantages in the characterization of metabolites in untargeted metabolic phenotyping [42][43][44].…”
Section: Endogenous Metabolite Identificationmentioning
confidence: 67%
“…Like many others [39][40][41], we have observed that the addition of IM provides many advantages in the characterization of metabolites in untargeted metabolic phenotyping [42][43][44].…”
Section: Endogenous Metabolite Identificationmentioning
confidence: 67%
“…In metabolomics, the sensitivity gain provided by micro-LC has been exploited to design rapid separations for metabolic phenotyping. Throughput has been optimized at the expense of chromatographic performance, providing fit for purpose platforms with enhanced but not maximized sensitivity upon miniaturization. A systematic comparison to conventional HPLC methods in terms of LOD and LLOQ was beyond the scope of these studies. Short micro-ultraperformance (UPLC) type of separation utilizing RP materials with sub-2-μm particles (100% wettable, 1.0 × 50 mm, 1.7 μm) and separation times of 2.5 min was successfully applied in large scale phenotyping studies and recently explored in combination with ion mobility. , A rapid micro-HILIC method utilizing sub-2-μm particles (Acquity UPLC BEH-Amide, 1.0 × 50 mm, 1.7 μm) addressed the analysis of polar metabolites in rat urine in less than 3.5 min.…”
Section: Navigating the Conflicting Goals Of Metabolome Coverage And ...mentioning
confidence: 99%
“…Throughput has been optimized at the expense of chromatographic performance, providing fit for purpose platforms with enhanced but not maximized sensitivity upon miniaturization. A systematic comparison to conventional HPLC methods in terms of LOD and LLOQ was beyond the scope of these studies. Short micro-ultraperformance (UPLC) type of separation utilizing RP materials with sub-2-μm particles (100% wettable, 1.0 × 50 mm, 1.7 μm) and separation times of 2.5 min was successfully applied in large scale phenotyping studies and recently explored in combination with ion mobility. , A rapid micro-HILIC method utilizing sub-2-μm particles (Acquity UPLC BEH-Amide, 1.0 × 50 mm, 1.7 μm) addressed the analysis of polar metabolites in rat urine in less than 3.5 min. Comparison to conventional HILIC-MS demonstrated 4-fold reduction of analysis time, 75% reduction in solvent consumption, and 18-fold reduction of sample consumption, while providing sufficient retention of polar metabolites (e.g.…”
Section: Navigating the Conflicting Goals Of Metabolome Coverage And ...mentioning
confidence: 99%